Analysis of the virgin state of stress at the Kiirunavaara mine - Sandström, Daniel (Luleå, 2003)
The mining production in Kiruna is heading towards larger depth and it is necessary to prepare for the next generation of underground facilities and new mining methods below the current main level. An important issue is the increasing rock stresses, which follows the ever-increasing depth of mining. This may result in instability of drifts, ramps, shaft and other facilities. The objective of this thesis is to clarify the stress situation in the mine and to state a relationship that could be used for rock mechanical analysis. The first part of the thesis is an appraisal of the results from the rock stress measurements carried out during the 1980's and 1990's. The measured state of stress shows a large variation, which depends on the influence of the mining production, measuring errors, and the heterogeneous nature of the rock mass. Even though, the stress measurements clearly affected by the mining production is sorted out, the variation remains. This means that the stress state in Kiirunavaara is still difficult to interpret. In order to increase the understanding of the natural variation, a literature review and analyses of the stress distribution in the rock mass is given. Because of this uncertainty, the second part presents another approach of handling the problems with the large scatter in the measured state of stress. By doing conceptual numerical analyses and probabilistic sensitivity analyses of underground constructions, the parameters affecting the behavior of the rock mass are studied. The analyses shows that the significance of the variation of the stress state is less than the significance of many other parameters like the stiffness and the strength of the rock mass. The recommendations is therefore, that a geomechanical model of the mine should be developed including for instance, the spatial variation of parameters like Young's modulus and strength of intact rock and joint parameters like number of joint sets, orientation, frequency and filling material. Godkänd; 2003; 20070218 (ysko)